Family and nursery - pillars of education for work among Vietnamese nursery children = Rodzina i przedszkole - filary edukacji do pracy wietnamskich dzieci w wieku przedszkolnym - Wołk, Zdzisław; Nguyen, Nhu Ngoc (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Professional work is one of the key developmental challenges faced by people nowadays, and preparation for entering the world of work requires actions taken from the earliest stages of life. Throughout different historical periods, cultures, and social systems, work has been ascribed different meanings and diverse approaches to preparing individuals for a future professional career have been developed.
Keywords: praca; dziecko w wieku przedszkolnym; edukacja do pracy; tradycja; rodzina; przedszkole; system edukacyjny; work; preschool child; education for work; tradition; family; kindergarten; education system